A study of psychological impact on adolescent children of parents with alcohol use disorder - Shwetali Dilip Gholap; Vivek Bapurao Chavan; Arvind Vishwambhar Karad; Manjeet Sureshkumar Santre (Annals of Indian Psychiatry, 2023)
Context: Children of alcoholics face risks of problem behavior during childhood and mental health problems in adult life. Identifying these problems at the earliest can significantly reduce the problems in future. Aim: We aimed to study psychological impact on adolescent children of parents with alcohol use disorder. Settings and Design: This is a cross-sectional study done at a tertiary care hospital in Maharashtra. Materials and Methods: Convenience sampling technique was used. One hundred adolescent children of alcohol use disorder patients were evaluated for problem behavior and perceived stress using the Child Behavior Checklist (CBCL) and Perceived Stress Scale, respectively. Current status of severity of alcohol use in parents was assessed using the Severity of Alcohol Dependence Questionnaire. Statistical Analysis Used: Data were analyzed using the Statistical Package for the Social Sciences Software Package (version 20.0). Results: In our study, we found that children whose fathers had severe alcohol dependence were exhibiting more externalizing behavior on CBCL and higher perceived stress and it was statistically significant. Conclusion: A positive correlation was found between severity of alcohol use in fathers and problem behavior in children.